PENGARUH EARNING PER SHARE (EPS) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM - Dini Arifian; Nurul Azizah (The Asia Pacific Journal Of Management Studies, 2019)
The stock price is a reflection of the company's performance. Basically, investors measure the company's performance in managing its resources to generate profits. To assess company performance, investors need to analyze first before investing by using several benchmarks, namely ratios. This study aims to examine the effect of the ratio of Earning Per Share and Debt to Equity Ratio to Share Prices on food and beverage companies on the Indonesia Stock Exchange (IDX) for the 2013-2018 period.This research is an empirical study, where the data used in this study are secondary data. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX) in the period 2013 to 2018, amounting to 18 companies. the number of samples used in this study were 6 companies with a sampling technique using purposive sampling. The classic assumption test in this study uses the normality test, the multicollinearity test, the heterokedasticity test and the autocorrelation. Data analysis uses multiple linear analysis, autocorrelation test, F test (F test), T test (T test) and coefficient of determination test. Data analysis using SPSS20 software.The results of research for Earning Per Share show a significant value of 0,000 which means there is a significant influence on the Stock Price, Debt to Equity Ratio shows a significant value of 0.201 which means no effect on the Stock Price. The coefficient of determination shows a value of 71,4% while the remaining 28,6% is influenced by other factors. From the results of the F test (F test) obtained 0,000 results which means that EPS and DER simultaneously have a significant effect on stock prices. This research is expected to provide useful information in making investment decisions.